PENGARUH MOTIVASI TERHADAP DISIPLIN KERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI JAMBI - M Zahari (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Research aims to understand motivation to influence the awareness of discipline in office industry and trade jambi and to know how big the influence of variable-variabel it is a partial and which between factors are most dominant widening opportunities for the awareness of discipline office Industry and Trade Jambi. In this research using methods descriptive analysis quantitative. Data to use is the primary data and data skunder obtained indirectly of the employees office Industry and Trade Jambi from the spreading the statement in the form of kuisioner regarding the motivation with each indicator affect increased the awareness of discipline office Industry and Trade Jambi and of data obtained from DISPERINDAG Jambi and data other supporting. In analyzed data used linear regression simple analysis .Through the testing t to know the motivation to influence the awareness of discipline office Industry and Trade Jambi in a partial .Data mixed with the help of computer program spss.17.0. Based on the results of penelitain, then found the size of the influence variable motivation on increased discipline work is as much as 60,1 % and the rest 39,9 % in are caused by by varibel out peelitian this.As for the regression line y = a + bx, where when b increased by one % so will increase the increase in variable motivation of 7.674 %. Motivation have an influence fairly high evaluation official discipline office of industry and trade jambi this means employees has shown discipline attitude good against the rules of prevailingKeyword: motivation, discipline